Humor dalam Madihin John Tralala dan Hendra (Kajian Jenis Humor Perspektif Veatch, Gruner, dan Hobbes) - Rafiek, M. (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2018)
This study aims to describe and explain the types of humor in Madihin John Tralala and Hendra from Veatch, Gruner, and Hobbes perspectives. The method used in this research is descriptive qualitative with content analysis technique. The results of this study are (1) Tight answers humor based on the emotional transformation theory of Veatch, (2) Praise and jokes humor based on Hobbes' theory of excellence, (3) Defense, clarification, not to be outdone humor based on the theory of aggression from Gruner, (4) ) Narrative, association, and contradictory conditions humor according to the emotional transformation theory of Veatch, (5) Rhetorical questions humor based on aggression theory of Gruner, and (6) Association humor according to emotional transformation theoryof Veatch.